Using nominal group technique to investigate the factors of child sexual abuse in Malaysia - Che Rozubi, Norsayyidatina; Anuar, Azad Athahiri; Gaitis, Konstantinos Kosmas; Ismail, Nurul Khairani (Institute of Advanced Engineering and Science, 2024)
This study aims to study the factors contributing to sexual abuse of children in Malaysia. This study uses the nominal group technique (NGT) approach in determining the list of factors for victims and predators, involving six experts from six different institutions that are directly involved with the issue of child sexual abuse (CSA). The findings of the study show that there are four factors that reach the highest value (86.7%) for the victims, which are naivety and lack of knowledge, family problems, unsafe environment, and social media. As for predator factors, two factors were rejected because they reached a low value, namely the factor of “wanting to try” (60%), and mental health issues (66.67%). Finally, the highest predator factors found are family crisis and upbringing style, with each reaching a value of 83.33%. The findings of the study show that several factors in the occurrence of sexual abuse against children can be identified. This matter needs attention so that this problem can be controlled and prevented from spreading in the community. The NGT method shows an effective and acceptable methodology for solving the problems of this study.